2015
DOI: 10.11594/jtls.05.02.08
|View full text |Cite
|
Sign up to set email alerts
|

Gametophyte Morphology and Development of Six Species of Pteris (Pteridaceae) from Java Island Indonesia

Abstract: The morphology of sporophyte, the type of reproduction, and cytology of Pteris had been reported, while the gametophyte morphology of Pteris in Java island has not been studied yet. The objective of this study was to describe the gametophyte morphology and development of P. biaurita, P. ensiformis, P. exelsa, P. longipinnula, P. tripartita, and P. vittata in Java island. Spores were obtained from fertile leaves of Pteris plants originated from several locations in Java island. The number of spores per sporangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
1
0
5
Order By: Relevance
“…This result is in accordance to the previous study [19] that showed the gametophyte cells would continue to proliferate along with the age of the gametophyte and the total number of the proliferating cell was varied among species.…”
Section: Mature Gametophytesupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in accordance to the previous study [19] that showed the gametophyte cells would continue to proliferate along with the age of the gametophyte and the total number of the proliferating cell was varied among species.…”
Section: Mature Gametophytesupporting
confidence: 93%
“…The medium was put in a plastic box, covered with a paper filter, and sterilized using boiling water and cool it down for one night, then as many as 0.003 g spores for each treatment were sown on media [19]. Growth and development of gametophytes were observed using stereo microscope once a week for and repeatedly under 10× for each treatment.…”
Section: Gametophyte Growth and Development Observationmentioning
confidence: 99%
“…Se han publicado varios estudios de la fase gametofítica del género de varias especies entre los que destacan las investigaciones de (Mehra, 1938) p. 202-210;(Crotty, 1967) p.105-117; (Cohen & Crotty, 1979) p. 179-182;(Laird & Sheffield, 1986) p. 139-143;(Gremmrich, 1988) p. 159-164; (Beri & Bir, 1993) p. 73-78;(Mendoza, Pérez-García, Reyes-Jaramillo, & Ricci, 1995) p. 51-57; (Huang, Chou, Hsieh, Wang, & Chiou, 2006) p. 261-268; (Letelier & Penailillo, 2007) p. 93-97; (Prada, Moreno, & Gabriel y Galan, 2008) p. 14-25; (Zhang, Shi, Zhang, & Jiang, 2008) p. 33-41; (Tanco, Martínez, & Bonomo, 2009) p. 10-17; (Martínez, 2010) p. 89-102; (Huang, Hsu, S-Y., Hsieh-Mei, & Chiou, 2011) p. 79-87;(Chao, Lui, Chiang, & Chiou, 2012) p. 1-7; (Martínez, Prada, Tanco, & Bonomo, 2013) p. 46-52; (Baskaran, Jeyachandran, & Meighias, 2014) p. 2350-2358; (Puspitasari, Chikmawati, & Praptosuwiryo, 2015) p. 98-104.…”
Section: Antecedentesunclassified
“…Pengamatan tipe reproduksi dilakukan untuk memperoleh sampel dengan tipe reproduksi seksual. Pengamatan dilakukan dengan penghitungan jumlah spora pada satu sporangium mengikuti Puspitasari et al (2015). Satu sporangium diletakkan di atas kaca benda yang telah ditetesi air, kemudian ditutup dengan kaca penutup.…”
Section: Pengamatan Tipe Reproduksiunclassified
“…Media tumbuh yang disiapkan, terdiri dari vermiculite, gambut, dan perlite (Puspitasari et al 2015). Sebanyak 3 komposisi perlakuan media diuji, yaitu media pertama (M1) terdiri dari vermiculite:lumut sphagnum:perlite, dengan perbandingan 2:2:1; media kedua (M2) terdiri dari vermiculite:perlite, dengan perbandingan 2:1; media ketiga (M3) terdiri dari vermiculite:lumut sphagnum, dengan perbandingan 1:1.…”
Section: Pengamatan Pertumbuhan Dan Perkembanganunclassified